2020
DOI: 10.11005/jbm.2020.27.2.125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Postoperative Muscle Strength Using Surface Electromyography in Hip Fracture Patient

Abstract: Background: To compare the muscle strength of patients with a hip fracture according to the presence of sarcopenia after surgery and the correlation of measured values between a Biodex and surface electromyography (sEMG) in postoperative measurement of muscle strength. Methods: Seventy-one patients who underwent hip fracture surgery were included in this study. Muscle mass was measured using dual energy X-ray absorptiometry and the grip strength was evaluated using a dynamometer. The diagnosis of sarcopenia fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…24,25 Low muscle mass and weak muscle strength of sarcopenic hip fracture patients are associated with this higher mortality. 26 One recent position statement of an expert panel questioned the association between lean muscle mass and adverse health-related outcomes in older adults. 7,27 Thus, identification of optimal diagnostic criteria of sarcopenia is crucial to evaluate the risk of mortality of hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Low muscle mass and weak muscle strength of sarcopenic hip fracture patients are associated with this higher mortality. 26 One recent position statement of an expert panel questioned the association between lean muscle mass and adverse health-related outcomes in older adults. 7,27 Thus, identification of optimal diagnostic criteria of sarcopenia is crucial to evaluate the risk of mortality of hip fracture patients.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, the 1‐year mortality rate is more pragmatic than the 5‐year mortality rate in hip fracture patients because up to 59% of these patients die within 1‐year after the trauma 24,25 . Low muscle mass and weak muscle strength of sarcopenic hip fracture patients are associated with this higher mortality 26 . One recent position statement of an expert panel questioned the association between lean muscle mass and adverse health‐related outcomes in older adults 7,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, development of tools for assessment of muscle strength for diagnosis of sarcopenia in postoperative patients with hip fractures is needed. Although surface electromyography (sEMG) has been used for assessment of muscle strength in patients with hip fractures, a standardized protocol for assessment of muscle strength in patients with hip fractures has yet to be established 31) . A standardized method for measurement of muscle strength for treatment of sarcopenia in patients with hip fractures should be developed in the future.…”
Section: Diagnostic Criteria For Sarcopeniamentioning
confidence: 99%
“…As highlighted by the state of the art introduced above, sEMG is widely used for the analysis of specific pathologies but very few works in the literature have focused on the use of sEMG for the assessment of sarcopenia or its monitoring over time. For example, the study proposed in [ 25 ] compared the muscle strength of seventy-one hip fracture patients based on the presence of sarcopenia after surgery and correlated the measured values between sEMG and dynamometer in the postoperative measurement of muscle strength. After the trial, the authors concluded that dynamometer and sEMG values were highly correlated, although no statistically significant difference in muscle strength with or without sarcopenia was evidenced.…”
Section: Introductionmentioning
confidence: 99%